Reducing trade costs in LDCs: The role of Aid for Trade - Rainer Lanz; Michael Roberts; Sainabou Taal (World Trade Organization (WTO), 2016)
This study analyses the role of Aid for Trade in reducing trade costs in least developed countries (LDCs). The analysis builds on questionnaires and case stories submitted as part of the Aid-for-Trade monitoring and evaluation exercise for the Fifth Global Review of Aid for Trade. Trade costs are high in LDCs and constitute a major impediment to their participation in international trade. The most important sources of trade costs in LDCs are inadequate transport infrastructure, cumbersome border procedures and compliance with non-tariff measures for merchandise exports. In the case of LDC services exports, major drivers of trade costs include ICT networks, poor regulation, low skill levels, the recognition of professional qualifications and restrictions on the movement of natural persons. LDCs are well aware of the issue of high trade costs, which is addressed by more than 90% of LDCs in their national strategies. Trade facilitation is the top Aid-for-Trade priority for LDCs, which is also reflected in increasing Aid-for-Trade flows. The analysis of questionnaires, case stories, diagnostic trade integration studies and existing econometric work illustrates the important role played by Aid-for-Trade interventions in lowering trade costs in LDCs.
Keywords: F13; F35; F63; 330; trade costs; aid for trade; trade facilitation; least developed countries